Science and Mathematics Teachers' Integration of TPACK in STEM Subjects in Qatar: A Structural Equation Modeling Study - Nasser Mansour; Ziad Said; Mustafa Çevik; Abdullah Abu-Tineh (MDPI AG, 2024)
This study aimed to explore how secondary school science and mathematics teachers in Qatar integrate Technological Pedagogical Content Knowledge (TPACK) into their teaching practices. The study examined the relationships between the subcomponents of TPACK using structural equation modeling (SEM), complemented by an analysis of additional categorical variables. A total of 245 science and mathematics teachers from Qatar participated in the research. The model's findings showed that the internal components-technological knowledge, pedagogical knowledge, and content knowledge-had a significant and positive direct effect on the external factors: technological pedagogical knowledge, technological content knowledge, and pedagogical content knowledge. However, these internal components did not directly impact TPACK itself. Together, these variables accounted for 77% of the variance in TPACK. Among the findings, Technological Content Knowledge (TCK) emerged as one of the most influential variables affecting TPACK, emphasizing its importance in teachers' TPACK integration. On the other hand, it was found that Pedagogical Content Knowledge (PCK) did not have a direct and significant effect on TPACK. Categorical variables like certificates and postgraduate education significantly impact TPACK and its subcomponents, while gender, field of study, and teaching experience do not. This finding underscores the importance of structured training and postgraduate education in enhancing TPACK skills for science and mathematics teachers. Participation in technology-based certification programs and postgraduate studies in STEM is crucial for their TPACK development in teaching STEM subjects. Future studies could explore the long-term impact of structured, technology-based training programs on enhancing STEM teachers' TPACK development and assess how this improvement influences student learning outcomes in science and mathematics classrooms. This would provide deeper insights into the effectiveness of such programs and their potential to transform teaching practices and student achievement in STEM education.